Machine Learning Based Opioid Overdose Prediction Using Electronic Health Records - Dong, Xinyu; Rashidian, Sina; Wang, Yu; Hajagos, Janos; Zhao, Xia; Rosenthal, Richard N; Kong, Jun; Saltz, Mary; Saltz, Joel; Wang, Fusheng (AMIA ... Annual Symposium proceedings, 2019)
Opioid addiction in the United States has come to national attention as opioid overdose (OD) related deaths have risen at alarming rates. Combating opioid epidemic becomes a high priority for not only governments but also healthcare providers. This depends on critical knowledge to understand the risk of opioid overdose of patients. In this paper, we present our work on building machine learning based prediction models to predict opioid overdose of patients based on the history of patients' electronic health records (EHR). We performed two studies using New York State claims data (SPARCS) with 440,000 patients and Cerner's Health Facts database with 110,000 patients. Our experiments demonstrated that EHR based prediction can achieve best recall with random forest method (precision: 95.3%, recall: 85.7%, F1 score: 90.3%), best precision with deep learning (precision: 99.2%, recall: 77.8%, F1 score: 87.2%). We also discovered that clinical events are among critical features for the predictions.